Magnum Bonum; Or, Mother Carey's Brood - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"Magnum Bonum; Or, Mother Carey's Brood" by Charlotte M. Yonge is a fictional novel likely written in the late 19th century. The narrative centers around the lives of the Brownlow family, particularly focusing on Joseph Brownlow, his widowed mother, and a young orphan girl named Caroline Allen, who becomes a significant part of their household and ultimately a beloved member of the family. The book delves into themes of compassion, love, and the dynamics of family life. At the start of the story, we are introduced to Joe Brownlow, who advocates for inviting Miss Allen to spend her holidays with them as she has no home. He reminisces about his own childhood association with her family's struggles and instantly feels a sense of duty towards her. The opening chapters set the stage for Caroline's arrival at the Brownlow household, highlighting her innocence, charm, and the deep sense of wonder she feels upon experiencing care and beauty for the first time. Mrs. Brownlow, Joe's mother, showers love and kindness on Caroline, and simultaneous hints at a budding romance between Joe and Caroline create an engaging backdrop for the unfolding familial relationships and new beginnings. The narrative captures both heartbreak and hope, promising an exploration of life$1 (Bs challenges and joys as it develops. (This is an automatically generated summary.)s
Release date is 2004-02-01
Produced by Sandra Laythorpe and David Widger
Keywords: England -- Social life and customs -- 19th century -- Fiction; Domestic fiction; Religious fiction